Building multicultural education that tolerates religious diversity - Abdul Sulaiman (Universitas Islam Malang, 2021)
Islamic religious education, including subjects that must be given to students who are Muslim, even though these students study at non-Islamic schools. Likewise, on the other hand, Islamic schools must also facilitate religious education in accordance with the religions of their students. Santo Paulus Catholic High School Jember, including a school that facilitates Islamic religious education for Muslim students. Uniquely, there is a religiosity subject, which includes all universal values in the official religion in Indonesia. The focus of this research is, how is the portrait and dynamics of Islamic religious education in non-Muslim schools (Catholic schools)? In this context, the authors chose a qualitative approach in data mining and processing. Interviews, document studies, observation, data research are the techniques chosen in research data collection. The research findings: 1) SMA Catholic Santo Paulus Jember has 6 Islamic religious education teachers, but they are not in accordance with the qualifications of the subjects they are teaching, 2) apart from PAI subjects, SMA Catholic Santo Paulus Jember strengthens students with religiosity lessons, namely lessons which includes universal values of all religions, 3) SMA Catholic Santo Paulus Jember is in demand by students from the six official religions in Indonesia.